Evaluation of antibody responses in healthy individuals receiving SARS-CoV-2 inactivated vaccines - Ziyu Liu; Liyan Cai; Man Xing; Nan Qiao; Jiaojiao Liu; Xuejun Li; Chiyu Zhang; Naijun Tang; Zhelong Xu; Yingying Guo; Renfei Lu; Dongming Zhou (Elsevier, 2024)
Inactivated coronavirus disease 2019 (COVID-19) vaccines such as CoronaVac and BBIBP-CorV have been widely used in China. However, more investigation is still needed to understand antibodies' duration and effectiveness against severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) variants in the real world. In this study, 575 participants who had been vaccinated with two or three doses of the inactivated vaccine were recruited. Serum samples were collected and tested for anti-spike IgG and neutralizing antibodies against SARS-CoV-2 (original strain, Dela, and Omicron). Unsurprisingly, a third dose of the vaccine significantly enhanced antibody responses against SARS-CoV-2 and its variants. However, despite a booster dose, the neutralizing antibody levels against Omicron, particularly the BA.5.2 subvariant, remained low. There was no sex bias, but an age bias was observed. Notably, the predominant IgG subclass antibodies were IgG1 and IgG2, with a much lower level of IgG4. After the booster shot, the ratio of IgG4 to IgG1 significantly increased. The observation of IgG1 to the IgG4 class switch after repeated inactivated vaccinations underscores the importance of continuous monitoring of subclass antibody responses. Further clinical investigations are required to understand the implications of this class switch for optimizing immunization strategies.